Clinical validity of plasma and urinary desmosine as biomarkers for chronic obstructive pulmonary disease. Issue 6 (16th January 2012) - Huang, Jeffrey T-J; Chaudhuri, Rekha; Albarbarawi, Osama; Barton, Alun; Grierson, Christal; Rauchhaus, Petra; Weir, Christopher J; Messow, Martina; Stevens, Nicola; McSharry, Charles; Feuerstein, Giora; Mukhopadhyay, Somnath; et al.
Abstract : Background: Although an increased concentration of degraded elastin products in patients with chronic obstructive pulmonary disease (COPD) has been reported for many years, its clinical validity and utility remain uncertain due to technical difficulties, small study groups and the unknown relationship between exacerbation and elastin degradation. The objectives of this study were to determine the validity of urinary and blood total desmosine/isodesmosine in patients with COPD and asthma and to evaluate their relationship to exacerbation status and lung function. Methods: Urinary and blood desmosine levels were measured using validated isotopic dilution liquid chromatography–tandem mass spectrometry methods. Results: 390 study participants were recruited from the following groups: healthy volunteers, stable asthma, stable and 'during an exacerbation' COPD. Compared with healthy non-smokers, we found increased urinary or blood desmosine levels in patients with COPD, but no differences in patients with asthma or healthy smokers. The elevation of urinary desmosine levels was associated with the exacerbation status in patients with COPD. Approximately 40% of patients with stable and 'during an exacerbation' COPD showed elevated blood desmosine levels. Blood desmosine levels were strongly associated with age and were negatively correlated with lung diffusing capacity for carbon monoxide. Conclusion: The results suggest that urinary desmosine levels are raised by exacerbations of COPD whereas blood desmosine levels are elevated in a subgroup of patients with stable COPD and reduced lung diffusing capacity. The authors speculate that a raised blood desmosine level may identify patients with increased elastin degradation suitable for targeted therapy. Future prospective studies are required to investigate this hypothesis.